Arrest of progression of pre‐induced abdominal aortic aneurysm in apolipoprotein E‐deficient mice by low level laser phototherapy. Issue 10 (19th November 2014) - Gavish, Lilach; Beeri, Ronen; Gilon, Dan; Rubinstein, Chen; Berlatzky, Yacov; Bulut, Atilla; Reissman, Petachia; Gavish, Leah Y.; Gertz, S. David
<x xml:space="preserve">Abstract</x> Background and Objectives Using non‐invasive, high‐frequency ultrasonography (HF‐u/s), we showed that low‐level laser phototherapy (LLL) inhibits de‐novo formation of abdominal aortic aneurysms (AAA) in apolipoprotein‐E‐deficient (Apo‐E‐/‐) mice. The current study tests the effect of LLL on the progression of pre‐induced AAA. Study Design/Material and Methods AAA was induced in Apo‐E‐/‐ mice (age16–20 weeks) by subcutaneous infusion of angiotensin‐II using osmotic minipumps (1000 ng/kg/minutes, 4 weeks). HF‐u/s (40 MHz, 0.01 mm resolution, Vevo‐770, VisualSonics) was used to measure the maximum cross‐sectional‐diameter (MCD) of the suprarenal abdominal aorta, the anterior wall displacement (AWD), and radial wall velocity (RWV). The aortas of mice that developed >35% dilatation at 2 weeks over baseline were exposed retroperitoneally and treated with LLL (780 nm, 2.2 J/cm2, 9 minutes) or sham‐operated. HF‐u/s was repeated at 4 weeks, the mice sacrificed by perfusion fixation, and the aortas excised for histopathology. Results Of all mice with >35% MCD expansion of the suprarenal aorta at 2 weeks, 7(58%) of 12 non‐treated, but only 1(7%) of 14 LLL, had increased MCD(> 1 SD) at 4 weeks (P < 0.009 by Fisher's Exact Test [FET]). The mean change in MCD from 2–4 weeks was also markedly reduced in the LLL‐treated mice (control vs. LLL, 0.24 ± 0.25 vs. −0.06 ± 0.39mm, P = 0.029 by unpaired t‐test). Similar results were obtained when limiting the analysis to animals with ≥50% expansion at 2 weeks. The deterioration in AWD from 2–4 weeks in non‐treated controls was not observed in LLL‐treated animals (ΔAWD: control, 0.03 ± 0.05 mm, P < 0.036 vs. LLL, 0.00 ± 0.05, P = 0.91 by paired t‐test). By the modified Daugherty classification, we found significantly fewer severe aneurysms at 4 weeks in the LLL‐treated animals versus control (3 of 10 vs. 9 of 11, P = 0.03 by FET). Conclusions LLL not only prevents de novo development of AAA, but, from this study, also arrests further progression of pre‐induced AAA and its associated deterioration in the biomechanical integrity of the aortic wall in Apo‐E‐/‐ mice. Lasers Surg. Med. 46:781–790, 2014. © 2014 Wiley Periodicals, Inc.